Stressful integration - Oded Stark (University of Tübingen, Faculty of Economics and Social Sciences, 2013)
This paper considers the integration of economies as a merger of populations. The premise is that the merger of groups of people alters their social landscape and their comparators. The paper identifies the effect of the merger on aggregate distress. A merger is shown to increase aggregate distress, measured as total relative deprivation: the social distress of a merged population is greater than the sum of the social distress of the constituent populations when apart. Physiological evidence from neighboring disciplines points to an increase in societal stress upon merger.
urn:nbn:de:bsz:21-opus-68808
Keywords: D04; D63; F55; H53; P51; 330; Merger of populations; Revision of social space; Aggregate relative deprivation; Societal distress